2017
DOI: 10.1007/s00384-017-2949-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of the iliac arteries: a marker for leakage risk in rectal anastomosis—a blinded clinical trial

Abstract: Calcification in the iliac arteries appears to be a good marker for the risk of leakage after rectal anastomosis. The calcification scoring system is easy to calculate after computed tomography and may aid in patient selection to create a protective ileostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Studies examining vascular calcification in colorectal anastomotic leakage have produced similarly variable results, which found no association between calcification and AL[28-31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining vascular calcification in colorectal anastomotic leakage have produced similarly variable results, which found no association between calcification and AL[28-31].…”
Section: Discussionmentioning
confidence: 99%
“…One study [20] was excluded on the basis that the cohort was included in a more recent study [26]. A total of 9 publications including 2002 patients were included in the qualitative review [21,22,[26][27][28][29][30][31][32].…”
Section: Study Selectionmentioning
confidence: 99%
“…Study characteristics are displayed in Table 1. Four studies [21,22,26,31] examined the relationship between aortic calcification and anastomotic leak in patients undergoing oesphagectomy for cancer (n=1446) and five studies [27][28][29][30]32] were undertaken in patients undergoing colorectal resection for benign disease or cancer (n=556). No studies of AC in patients undergoing gastric resection were identified.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…For rectal surgery, Pochhammer et al . studied 139 patients and reported that calcification in the iliac arteries was associated with leakage after rectal anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown an increased association with AL after colorectal surgery and oesophagectomy. For rectal surgery, Pochhammer et al [27] studied 139 patients and reported that calcification in the iliac arteries was associated with leakage after rectal anastomosis.…”
Section: Introductionmentioning
confidence: 99%